2020
DOI: 10.1111/rda.13610
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of deoxynivalenol‐induced apoptosis of sow ovarian granulosa cell

Abstract: Litter size is one of the most important economic traits in pig production. Recent studies identified that deoxynivalenol (DON), a widespread toxin in fodder, was associated with animal prolificacy. However, the underlying mechanisms have not yet been completely elucidated. Here, we used porcine ovary granulosa cells (pGCs) as a vector to establish DON concentration–time models and performed cell morphology and transcriptome analysis to identify and analyse the effects of DON on reproductive performance in swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Significant economic losses in pork production also result from the influence of DON on reproductive performance [ 19 , 20 , 21 ] when the developing fetus is exposed due to pregnant sows ingesting a toxin-contaminated diet [ 22 , 23 ]. However, a subsequent detailed study showed that no pathomorphologically or immunohistochemically detectable alterations occur in fetal organs after intrauterine transfer of DON [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant economic losses in pork production also result from the influence of DON on reproductive performance [ 19 , 20 , 21 ] when the developing fetus is exposed due to pregnant sows ingesting a toxin-contaminated diet [ 22 , 23 ]. However, a subsequent detailed study showed that no pathomorphologically or immunohistochemically detectable alterations occur in fetal organs after intrauterine transfer of DON [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in vitro studies on sow granulosa cells have shown that DON, at concentrations ranging from 500 to 2000 μg/L, induces a dose-dependent escalation in apoptotic rates compared to controls (M. Yang et al, 2020). Comparable findings were noted in another study where bovine granulosa cells exposed to DON at 100 ng/mL over a span of 4 days exhibited a 15% increase in apoptotic cells (Guerrero-Netro et al, 2015).…”
Section: Immunohistochemical Analysesmentioning
confidence: 83%
“…This toxin impairs porcine oocyte maturation by inducing nuclear anomalies, disturbing meiotic spindle structures, escalating oxidative stress, triggering autophagy, promoting apoptosis, and instigating epigenetic modifications (Alm et al, 2002;Han et al, 2016;Lan et al, 2018;Malekinejad et al, 2007;Schoevers et al, 2010). Moreover, DON exposure in porcine granulosa cells affects cell proliferation, steroidogenesis, apoptosis, and key metabolic pathways (Medvedova et al, 2011;Ranzenigo et al, 2008;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the cells were treated with 2,5-HD (0 mmol/L, 20 mmol/L, 40 mmol/L, 60 mmol/L) at 37 °C for 24 h, and the same growth cell culture medium was used to treat the control group (three biological repeats in both the treatment and control groups). The dose and reagent treatment time used in this experiment were based on previous studies that revealed the toxic effects on rat and sows’ ovarian granulosa cells [ 20 , 21 ] in vitro using this concentration and time.…”
Section: Methodsmentioning
confidence: 99%